Hospital usage of TOXBASE in Great Britain: Temporal trends in accesses 2008 to 2015. (November 2018) - Pyper, K; Eddleston, M; Bateman, DN; Lupton, D; Bradberry, S; Sandilands, E; Thomas, SHL; Thompson, JP; Robertson, C
Aim: To examine temporal trends in accesses to the UK's National Poison Information Service's TOXBASE database in Britain. Methods: Generalized additive models were used to examine trends in daily numbers of accesses to TOXBASE from British emergency departments between January 2008 and December 2015. Day-of-the-week, seasonality and long-term trends were analysed at national and regional levels (Wales, Scotland and the nine English Government Office Regions). Results: The long-term trend in daily accesses increases from 2.8 (95% confidence interval (CI): 2.6–3.0) per user on 1 January 2008 to 4.6 (95% CI: 4.3–4.9) on 31 December 2015, with small but significant differences in population-corrected accesses by region ( p < 0.001). There are statistically significant seasonal and day of the week patterns ( p < 0.001) across all regions. Accesses are 18% (95% CI: 14–22%) higher in summer than in January and at the weekend compared to weekdays in all regions; there is a 7.5% (95% CI: 6.1–8.9%) increase between Friday and Sunday. Conclusions: There are consistent in-year patterns in access to TOXBASE indicating potential seasonal patterns in poisonings in Britain, with location-dependent rates of usage. This novel descriptive work lays the basis for future work on the interaction of TOXBASE use with emergency admission of patients into hospital.